Generally Speaking, Dentists Can't/Will not Treat Patients with Disabilities? - Steven P. Perlman; H. Barry Waldman (Wolters Kluwer Medknow Publications, 2010)
There are more than a half of a billion people in the world who are disabled as a conse-quence of mental, physical and sensory impairments. The issues related to the care of individuals with disabilities increasingly will impact on the eco-nomic and social realities throughout the world as increased numbers of individuals with disabilities continue to survive; in particular, individuals with developmental disabilities and the burgeoning geriatric populations. The question considered is whether dentists are able and willing to pro-vide needed services for patients with disabilities? The issues faced in the United States are used as examples in a commentary which reviews the barriers faced by dentists who would consider providing care to individuals with dis-abilities. Despite formidable obstacles, the fact is that many do provide needed care to many of these patients. The need is to expand the preparation of fu-ture dentists and augment the abilities of current practitioners.